The impact of training on the management of children with cough of the health workers’ knowledge, attitude and skills in the management of children with cough and breathing difficulties - Khayati, Fitriana Noor; Haryanti, Fitri; Laksnawati, Ida Safitri (International Journal of Research in Medical Sciences, 2017)
Background: The empowerment of the community through health workers is expected to help decrease the occurrence of pneumonia in children under five years old. The health workers need to be given the training about the management of children with cough and breathing difficulties to improve their knowledge, attitude and skills. This research aims to know the impact of training on the management of children’s cough toward the health workers’ knowledge, attitude and skills in the management of children with cough and breathing difficulties. Methods: It was a quasi experimental study with pre-post with control group design. The research is conducted to community health workers where the intervention group (n=40) and the control group (n=37) with purposive sampling. The intervention group has the training by the methods of lectures, simulations, case studies and demonstrations using audiovisual media and modules, whereas the control group does so by reading modules. Results: After 14 days, there is an increase in the value of knowledge (p<0.05), the value of attitude (p>0.05) and a decrease in the value of skills (p >0.05). Conclusions: Training on the management of children’s cough can improve the health workers’ value of knowledge, but not value of attitude and skills after the training.